235k views
0 votes
6m – 3 = 5 – (m + 39.5)

What is the solution of the equation shown

User Luator
by
4.8k points

2 Answers

5 votes

Explanation:

6m-m=5-3+39.5

5m=-37.5

m=7.5

User Fangxin
by
6.3k points
11 votes

Answer:

m= -4.5

Explanation:

Let's solve your equation step-by-step.

6m−3=5−(m+39.5)

Step 1: Simplify both sides of the equation.

6m−3=5−(m+39.5)

6m−3=5+−1(m+39.5)(Distribute the Negative Sign)

6m−3=5+−1m+(−1)(39.5)

6m−3=5+−m+−39.5

6m+−3=5+−m+−39.5

6m−3=(−m)+(5+−39.5)(Combine Like Terms)

6m−3=−m+−34.5

6m−3=−m−34.5

Step 2: Add m to both sides.

6m−3+m=−m−34.5+m

7m−3=−34.5

Step 3: Add 3 to both sides.

7m−3+3=−34.5+3

7m=−31.5

Step 4: Divide both sides by 7.

7m

7

=

−31.5

7

m=−4.5

User Dirtyvagabond
by
6.2k points